PEMIKIRAN TAUHID SYEKH MUHAMMAD MUHAJIRIN AMSAR ADDARY DALAM KITAB KARANGANNYA SYARH ALA MATN AL JAUHAROH - Faznah; Mursyidi, Wathroh (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
ABSTRACT Imam Al-Ghazali said that the most important thing as an essential capital to worship Allah is a deep understanding of religion. In fact, such understanding is a pillar of religion. The series of tawhid, faith, and sharia are reflected in civilized humans in this mortal life. Mistakes in understanding the study of monotheism are influenced by the process of getting information very quickly in modern times, which must be balanced with the ability to filter information and the correct sources of knowledge. The thoughts of previous scholars who were qualified in their knowledge are things that still continue and need to be studied and used as the main reference in the right of monotheism. Sheikh Muhammad Muhajirin wrote his thoughts based on his knowledge, which he got from teachers with a chain of transmission that was connected to the Prophet; the book of Matan Jauharoh is a work of tawhid from the famous scholar Sheikh Ibrahim Al-Laqoni, whose book has been studied and used as a reference in studying the science of tawhid. This research was conducted with a qualitative approach, with the Critical Discourse Analysis method; according to Fairclough, AWK focuses discourse attention on language, using discourse points to the use of language as a social practice more than individual activities or to reflect something. It aims to find out Sheikh Muhammad Muhajirin's thoughts on the study of tawhid, which he expressed in Syarh Ala Matn Jauharoh, in relation to discourse, practice, and his role in the study of tawhid. The results showed that Sheikh Muhammad Muhajirin's thoughts on the study of monotheism can be seen from the detailed explanation of each stanza he quoted, which he then reflected in the daily education process he carried out both to his students and the surrounding community.